Gene Regulation and Metabolism: Post-Genomic Computational Approaches - Julio Collado-Vides [editor ] (Computational molecular biology., 2002)
An overview of current computational approaches to metabolism and gene regulation, focusing on current computational approaches to understanding the complex networks of metabolic and gene regulatory capabilities of the cell. The contributors look well beyond the state of the art in computational biology to anticipate what biological research will be like in a post-genomic world.